1994
DOI: 10.1016/0014-5793(94)00312-2
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional role of the bc1 complex in plants Mitochondrial bc1 complex catalyses both electron transport and protein processing

Abstract: Nuclear encoded mitochondrial precursor proteins are cleaved to mature size products by the general mitochondrial processing peptidase (MPP). In contrast to non-plant sources where MPP is a matrix enzyme, the plant mitochondrial MPP is localised in the inner membrane and constitutes an integral part of the bc, complex of the respiratory chain. Core proteins of the complex are immunologically related and show high sequence similarity to the MPP subunits from non-plant sources. The bc, complex in plants is thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…This differs from the other import components examined, and it appears that the level of MPP follows that of a respiratory chain component rather than a protein import component. This is consistent with the fact that, in plants, MPP is integrated into the cytochrome bc 1 complex of the respiratory chain (18,19,21). The capacity for import via the general import pathway correlated with the abundance of the ␣ and ␤ subunits of MPP.…”
Section: Is the Reduced Capacity Of The General Import Pathway Under supporting
confidence: 83%
“…This differs from the other import components examined, and it appears that the level of MPP follows that of a respiratory chain component rather than a protein import component. This is consistent with the fact that, in plants, MPP is integrated into the cytochrome bc 1 complex of the respiratory chain (18,19,21). The capacity for import via the general import pathway correlated with the abundance of the ␣ and ␤ subunits of MPP.…”
Section: Is the Reduced Capacity Of The General Import Pathway Under supporting
confidence: 83%
“…Mutagenesis was performed using altered site-directed mutagenesis (Promega, Madison, WI) or quick-change site-directed mutagenesis (Stratagene) kits as per the manufacturer's instructions, and mutants were confirmed by sequencing. 35 S-Labeled alternative oxidase precursor protein was synthesized as described by Whelan et al (24). The mutations introduced were designated by the position relative to the start site of the mature protein, followed by the three-letter abbreviation for the amino acid introduced, i.e.…”
Section: Synthesis Of the Soybean Alternative Oxidase Precursor And Dmentioning
confidence: 99%
“…Whereas the protein import apparatus is generally well conserved across phylogenetic groups (Hewitt et al, 2011), particularly the pore-forming subunits, which display high levels of orthology (Dolezal et al, 2006;Carrie et al, 2010a), significant differences have been observed between the outer mitochondrial membrane protein import receptors of plants compared with yeast and mammals (Perry et al, 2006;Lister et al, 2007). Further differences include the location of the mitochondrial processing peptidase (MPP) in the cytochrome bc 1 complex (Braun et al, 1992;Glaser et al, 1994) in plants compared with yeast and mammals.…”
Section: Introductionmentioning
confidence: 99%
“…First, protein subunits in a respiratory chain complex have been reported to be involved in protein import, this was initially reported with the finding that a subunit of the matrix-located MPP (b-MPP) also functions as one of the core subunits of the cytochrome bc 1 complex in Neurospora crassa (Schulte et al, 1989). Further studies in plants revealed a unique evolutionary history for MPP in mitochondria (Braun et al, 1992;Glaser et al, 1994;Eriksson et al, 1996;Brumme et al, 1998;Glaser and Dessi, 1999), where the core subunits of plant cytochrome bc 1 complexes are bifunctional, acting as both a peptidase and as integral subunits of the cytochrome bc 1 complex (Braun et al, 1992;Eriksson et al, 1996). More recently, it has been reported that the succinate dehydrogenase subunit 3 in yeast is also a component of the TIM22 translocase and has an active role in the import of proteins via the carrier import pathway (Gebert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%